MENDAMAIKAN IMAN DAN KEADILAN: MENGINTERPRETASI ULANG AJARAN AL-QUR'AN UNTUK MEMERANGI PELECEHAN SEKSUAL DI PONDOK PESANTREN - Nadiatul Maziyyah Attarwiyah dan Alda Nihayatul A’rifah (Fakultas Ushuluddin dan Pemikiran Islam, Universitas PTIQ Jakarta, 2025)
Sexual violence in Islamic boarding schools (pesantren) is a critical issue that demands an in-depth study, given that pesantren, as religious-based educational institutions, should serve as safe spaces oriented toward the moral development of students (santri). This study aims to examine the phenomenon of sexual violence in pesantren, explore relevant Quranic values in constructing a protection system, and formulate effective prevention strategies. The research employs a qualitative approach with normative analysis, literature review of Quranic exegesis, and analysis of Quranic verses using Jürgen Habermas’ critical hermeneutics theory. The findings reveal that the Quran provides a strong ethical foundation through five key principles: protection of honor and dignity, justice, compassion and empathy, respect for individual rights, and the collective duty to prevent wrongdoing. Applying Habermas' critical hermeneutics demonstrates that these verses hold not only normative significance but also transformative potential in fostering critical awareness and collective social action. This analysis underscores that preventing sexual violence must be both structural and cultural, involving educational system reforms, institutional regulatory strengthening, and the internalization of Islamic values to build collective consciousness. Thus, this study asserts that the prevention of sexual violence in pesantren is not merely a moral and religious obligation but also an institutional responsibility that must be realized through an equitable education system based on Quranic values.